Numerical Study of Microbial Hydrogen Sulphide Generation in Hydrocarbon Reservoirs - SALAH HAGAR, HAITHM SALAH MOHAMMED (2021)
The present work aims to represent and predict microbial hydrogen sulphide generation and to investigate the effects of CO2 components on the souring process through reactive transport simulation and mathematical modelling. The influence of key parameters including CO2, salinity, and temperature on the microbial growth of sulphate reducing bacteria (SRB) is simulated using the kinetic and multispecies reactive transport simulator PHREEQC coupled with a multiphase Buckley Leverett model. Simulation results are then validated against some experimental data from the literature. To assess the role of each of the influential factors, a sensitivity analysis is performed at varying CO2 concentrations (4.403×10-4 - 52.24×10-4) mol/kgw, salinity 0.5-0.8 meq/ml (40000-27000ppm), and temperature 40-100 F (4.5-37.8°C). The resulting data are then used to mathematically relate CO2 concentration, salinity, and temperature to the concentration of hydrogen sulphide and souring onset time by applying response surface methodology (RSM). The results suggest that the souring onset time increases as the CO2 concentration increases (CO2 ≥ 52.24×10-4) and also as injection temperature and salinity increase. Higher temperatures are found to delay souring onset as the injection water salinity is increased. In Addition, a lower concentration of CO2 results in an early onset time if the temperature is kept low at 40-60 F (4.5-15.6°C). The findings also indicate that temperature and salinity will affect the hydrogen sulphide concentration. The highest hydrogen sulphide concentrations are observed when the temperature is ranged between 40-70 F (4.5- 21.1°C) under a salinity range between 0.5-0.65 meq/ml (40000-33000ppm). Moreover, CO2 has a significant effect on hydrogen sulphide concentration, where at temperatures between 40-70 F (4.5-21.1°C), higher hydrogen sulphide concentrations are obtained.